Fiscal Policy: Financing and Indebtedness - Jing Cynthia Wu; Shihan Xie; Yinxi Xie; Ji Zhang (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We conduct a large-scale information randomized controlled trial to study fiscal policy impacts. Surveying approximately 9,000 households across five eurozone countries with varying debt-to-GDP ratios enables a clean cross-country comparison. The key finding is that the fiscal multiplier depends jointly on the financing method and the country's debt burden: multipliers are smaller in high-debt countries when debt-financed but remain similar across countries when tax-financed. Finally, we develop a New Keynesian model featuring fiscal discipline, which reproduces the empirical patterns observed in the survey and highlights their underlying economic mechanisms.
Keywords: C83; D84; E62; H60; 330; survey RCT; fiscal multiplier; financing method; debt-to-GDP ratio